Perspectives on Organelle Interaction, Protein Dysregulation, and Cancer Disease - Díaz, Paula; Sandoval-Bórquez, Alejandra; Bravo-Sagua, Roberto; Quest, Andrew F. G.; Lavandero, Sergio (Frontiers in Cell and Developmental Biology, 2021)
In recent decades, compelling evidence has emerged showing that organelles are not static structures but rather form a highly dynamic cellular network and exchange information through membrane contact sites. Although high-throughput techniques facilitate identification of novel contact sites (e.g. organelle-organelle, organelle-vesicle interactions), little is known about their impact on cellular physiology. Moreover, even less in known about how the dysregulation of these structures impacts on cellular function and therefore, disease. Particularly, cancer cells display altered signaling pathways involving several cell organelles; however, the relevance of interorganelle communication in oncogenesis and/or cancer progression remains largely unknown. This review will focus on organelle contacts relevant to cancer pathogenesis. We will highlight specific proteins and protein families residing in these organelle-interfaces that are known to be involved in cancer-related processes. First, we will review the relevance of endoplasmic reticulum (ER)-mitochondria interactions. This section will focus on mitochondria-associated membranes (MAMs) and particularly the tethering proteins at the ER-mitochondria interphase, as well as their role in cancer disease progression. Subsequently, the role of Ca2+ at the ER-mitochondria interphase in cancer disease progression will be discussed. Members of the Bcl-2 protein family, key regulators of cell death, also modulate Ca2+ transport pathways at the ER-mitochondria interphase. Furthermore, we will review the role of ER-mitochondria communication in the regulation of proteostasis, focusing on the ER stress sensor PERK (PRKR-like ER kinase), which exerts dual roles in cancer. Second, we will review the relevance of ER and mitochondria interactions with other organelles. This section will focus on peroxisome and lysosome organelle interactions and their impact on cancer disease progression. In this context, the peroxisome biogenesis factor (PEX) gene family has been linked to cancer. Moreover, the autophagy-lysosome system is emerging as a driving force in the progression of numerous human cancers. Thus, we will summarize our current understanding of the role of each of these organelles and their communication, highlighting how alterations in organelle interfaces participate in cancer development and progression. A better understanding of specific organelle communication sites and their relevant proteins may help to identify potential pharmacological targets for novel therapies in cancer control.